PERANCANGAN PENJUALAN HANDPHONE ONLINE BERBASIS WEB MOBILE PADA CV RATU3G CELL KOTA LUBUKLINGGAU - Rudi Kurniawan (LPPM UNIVERSITAS BINA INSAN, 2016)
The author conducted research on CV Ratu 3G regarding selling mobile phones online through online sales. Mobile sales using a website are considered a good step and are the latest innovation in the business of buying and selling. The method used in this sale uses several tools such as Uml while the system development method uses